Knowledge of Pressure Ulcer Management among Nurses - Shrestha, Nisha; Shrestha, P (Journal of Gandaki Medical College-Nepal, 2017)
Background: Pressure ulcer (PU) development remains a significant complication among at-risk patients. It is considered “never events” because they are preventable and should “never” happen. It has been associated with increased morbidity, mortality, hospital cost and length of stay in the hospital. Prevention of pressure ulcers is considered a nurse-sensitive indicator hence nurses should have adequate knowledge about current evidence-based prevention and management of pressure ulcer. However, non adherence to these guidelines is frequent and lack of knowledge may act as barriers to using guidelines in clinical practice. Objectives: The objectives of the study were to 1. assess the knowledge of pressure ulcer management among nurses 2. determine the level of knowledge of pressure ulcer management among nurses 3. assess the association of knowledge of nurses and baseline variables. Methods: A descriptive cross sectional study was conducted, using pretested self administered questionnaire to assess the knowledge on pressure ulcer management among purposively selected 100 nurses working in Gandaki Medical College Teaching Hospital in 2015. Descriptive statistics as frequency and percentage were used and inferential statistics (Chi-square test) was done to find out association between knowledge and selected baseline variables. Results: The study revealed that 59% of the respondents had adequate knowledge where as 41% of nurse’s knowledge was found to be inadequate. Significant association was not found between age, working ward, experience, education, training, duration and knowledge of pressure ulcer management among Nurses. Conclusion: This result indicates that more than half of the nurses had the adequate knowledge but there is still need of education and training related pressure ulcer management. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, Page: 47-51